Metabolite profiling of pea roots in response to phosphate availability - Laparre, Jérôme (Landes Bioscience, 2011)
The arbuscular mycorrhizal (AM) symbiosis is a mutualistic association between soil fungi (Glomeromycota) and roots of most plant species. A recent study showed that high phosphate fertilization could inhibit mycorrhizal colonization at a very early stage, before hyphopodium formation. The authors proposed that inhibiting and/or stimulatory compounds might be present in roots grown under high phosphate or low phosphate, respectively. To further address this question, we performed metabolite profiling analyses of extracts of pea roots grown under low and high phosphate concentrations. Ultra high performance liquid chromatography (UHPLC) was coupled with high resolution (HR) mass spectrometry (Q-TOF) and multivariate statistical analysis. This allowed the detection of 34 ions discriminating the two conditions. A majority (28 ions) were more abundant in roots grown under low phosphate concentration, and among them four were specific of this condition. The results suggest that the regulation of AM symbiosis by phosphate may involve the synthesis or accumulation of stimulatory compounds in roots grown under low phosphate.